2001
DOI: 10.1034/j.1600-0463.2001.d01-140.x
|View full text |Cite
|
Sign up to set email alerts
|

A cellular model system of differentiated human myotubes

Abstract: The aim of this study was to select an effective and stable protocol for the differentiation of human satellite cells (Sc) and to identify the optimal time period for the experimental use of differentiated human Sc-cultures. In order to identify the differentiation conditions which give a good survival of myotubes and a high grade of differentiation, Sc-cultures were induced to differentiate in media supplemented with either 2% fetal calf serum (FCS) 2% horse serum (HS) or 10% HS. Based on higher CK-activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
109
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(115 citation statements)
references
References 24 publications
5
109
0
Order By: Relevance
“…Cell culture procedures and 2-DG uptake Human cell cultures from lean individuals were established as described previously [19][20][21] (Table 1). Cells were cultured in DMEM supplemented with 2% (vol./vol.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell culture procedures and 2-DG uptake Human cell cultures from lean individuals were established as described previously [19][20][21] (Table 1). Cells were cultured in DMEM supplemented with 2% (vol./vol.)…”
Section: Methodsmentioning
confidence: 99%
“…Finally, to evaluate GlcN effects on human skeletal muscle cells we used cultured human skeletal muscle cells that display several features of mature skeletal muscle and that have been previously used for studies of muscle metabolism [20]. In differentiated human muscle cells, GlcN induced a significant increase of both BIP/GRP78 and ATF6 mRNA levels (Fig.…”
mentioning
confidence: 99%
“…Studies performed in rodents have demonstrated that MyHC isoforms expressed in differentiated myotubes were identical to the MyHC expression pattern in the muscle fibers from which the satellite cells were isolated (Dusterhoft andPette, 1993, Rosenblatt, et al, 1996). In human muscle cell cultures it has been found that all myotubes in 8-day differentiated cell cultures were immunoreactive for fast MyHC, regardless of donor muscles having mixed MyHC expression in vivo (Gaster, et al, 2001) . In our hands, myotube cultures stained at day 8 after differentiation contained a noteworthy amount of slow muscle fibers as well (Fig.…”
Section: Fiber Type Comparisonmentioning
confidence: 99%
“…First, satellite cultures express traits known from in vivo muscles (16 -20), and second, they allow the genetic and adaptive processes to be differentiated (21). Recently, we described the optimized conditions for satellite culture proliferation and differentiation (19), which have been shown to be suitable for studying the regulation of glycogen synthase activity and the differentiation between induced and primary defects in glucose metabolism in diabetic and normal myotubes (20,21). In the present study, we measured palmitic acid uptake, oxidation, and incorporation into complex cellular lipids in myotubes established from type 2 diabetic subjects and matched control subjects to clarify whether myotubes established from the diabetic subjects expressed inherited defects in fatty acid metabolism.…”
mentioning
confidence: 99%
“…Cell culture. Cell cultures were established as previously described (19,20). In brief, muscle tissue was minced, washed, and dissociated for 60 min by three treatments with 0.05% trypsin-EDTA.…”
mentioning
confidence: 99%